About the Communicative Competence Formation in School Education: Work Experience - L. N. Bulygina (Russian State Vocational Pedagogical University, 2015)
The paper looks at the problems of fostering the teenagers' communicative competence in the light of the Federal State Educational Standards for Secondary Schools. The components of the above competence are emphasized along with the pedagogic conditions facilitating communication skills and abilities. The author summarizes the long-term pedagogic experience and recommends the procedure of step by step formation of communicative competence by way of interpreting the school subject knowledge. The complex of communicative tasks focused on mastering the communicative actions necessary for the teenagers' successful socialization is demonstrated, as well as the author's system of criterion level assessment of communicative competence acquisition, and recommendations for organizing the educational process and facilitating the competence development.